A superabsorbent nanocomposite based on sodium alginate and illite/smectite mixed‐layer clay. Issue 1 (8th March 2013) - Wang, Yizhe; Wang, Wenbo; Shi, Xiaoning; Wang, Aiqin
Abstract A series of superabsorbent nanocomposites were prepared by free radical grafting copolymerization of sodium alginate, partially neutralized acrylic acid (AA), styrene, and illite/smectite mixed‐layer clay (I/S). The structure and morphology of the nanocomposites were confirmed by Fourier transform infrared spectroscopy, X‐ray diffraction, and scanning electron microscope techniques. It was shown that the incorporation of I/S clearly enhanced the swelling properties of the nanocomposites. Various salts and surfactants showed remarkable effects on the swelling behaviors of the nanocomposites. Moreover, the nanocomposite exhibited better responsive and reversible on–off switching characteristics in pH 7.0 and 2.0 buffer solutions, which renders it promising for drug delivery application. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013